Hubungan Tingkat Pengetahuan Dan Efikasi Diri Dengan Pelayanan Kader Posyandu Lansia Di Desa Mancasan Kecamatan Baki - Kurniawan, Addin, Arif Widodo, A.Kep., M.Kes (2017)
Community empowerment is one of the efforts to create a society of healthy Indonesia, for example by involving members of the community to be a cadre of health. Kader Posyandu has a role as the actors of the health system, cadres are expected to provide a variety of health care services to the elderly. To be able to provide services posyandu maximum, cadres need to have a level of knowledge of good posyandu and has self-efficacy that support the performance of health cadres. This study aims to determine the relationship of the level of knowledge, self-efficacy with excellent service in the village cadres Posyandu Mancasan District of Baki. This research is descriptive correlative with cross sectional approach. The study population was all cadres who are in the working area of the District Mancasan Posyandu Elderly Village Tray numbering 40 people. Sample research as much as 40 cadres were obtained with total sampling technique. Collecting data using questionnaires, while data analysis using product moment correlation test. Conclusion The knowledge level cadres Posyandu elderly in the village Mancasan District of Baki largely sufficient, self-efficacy cadres Posyandu in the village Mancasan District of Baki largely being, services Posyandu in the village Mancasan District of Baki largely being, there is a significant relationship between the level of knowledge of self-efficacy and service cadres posyandu elderly in Rural Mancasan District of Baki, level of knowledge has a more dominant relationship of self-efficacy compared to services in the village cadres posyandu Mancasan District of Baki.